THE IMPACT OF A CASH DRIVEN HEALTH CARE SYSTEM ON BLOOD UTILIZATION : AN ANALYSIS OF BLOOD UTILIZATION DURING ELECTIVE SURGERIES AT THE UNIVERSITY OF NIGERIA TEACHING HOSPITAL ITUKU-OZALLA- A PILOT SURVEY - obinna ajuzieogu; adaobi o amucheazi; Richard Ewah (Mediterranean Journal of Hematology and Infectious Diseases)
One of the tasks of the anaesthetists includes making a decision on the need for blood transfusion during surgical procedure. This task though daunting in the face of epileptic blood supply, will save lives, but may result in over ordering and wasting of blood.